A ludicidade como recurso didático no processo de alfabetização e letramento nos anos iniciais - QUARESMA, Marcilene Costa (2024)
This study aims to study the importance of the use of playfulness in the process of literacy and letter in the early years of Elementary School. From the theoretical conceptions of Fortuna (2013); Cardoso (2000); Paiva (2003); Antunes (2005); Kishimoto (2008); Val (2006); Soares (2005); Silva (2004); Perez (2002); Ferreiro (1996); Soares (2009) and others, who gave me subsidies to study the study about playfulness, which is an indispensable didactic resource in the learning process of reading and writing. It is believed that even with all the difficulties observed in the school environment such as: physical structure, lack of didactic material and others, these teachers seek in their action-reflection-action a differentiated pedagogical make through games, toys and games, providing a pleasurable, concrete and meaningful education, so that the students can really be literate in the perspective of social practices. Then, a field survey was carried out with questionnaire application composed of 9 questions directed to the teachers of the 1st, 2nd and 3rd Years of the Literacy Cycle. As a result, it was noticed that the present teachers not only emphasized the concept of playfulness, but also their methodological applicability as a support in the process of learning to read and write, relating theory and practice in the school context.